The origin of exotic pet sugar gliders (Petaurus breviceps) kept in the United States of America - Campbell, Catriona D.; Pecon-Slattery, Jill; Pollak, Rebecca; Joseph, Leo; Holleley, Clare E. (PeerJ, 2019)
The demand for exotic non-domesticated animals kept as pets in the United States of America (USA) is increasing the exportation rates of these species from their native ranges. Often, illegal harvesting of these species is used to boost captive-bred numbers and meet this demand. One such species, the sugar glider (Petaurus breviceps), endemic to Australia and New Guinea is a popular domestic pet due to its small size and “cute” demeanour. Despite a legal avenue for trade existing in Indonesia, concerns have been raised that sugar gliders may be entering the USA from other parts of their native range where exportation is prohibited such as Australia, Papua New Guinea and the surrounding Indonesian islands. We compared previously published DNA sequences from across the native range of sugar gliders with samples collected from domestically kept sugar gliders within the USA to determine provenance and gene flow between source and introduced populations. Here we show that as predicted, the USA sugar glider population originates from West Papua, Indonesia with no illegal harvesting from other native areas such as Papua New Guinea or Australia evident in the samples tested within this study.
Keywords: Exotic pets; Sugar glider; Marsupials; Introduced species; Petaurus breviceps; Wildlife trade; Importation; Exportation; Mammals